2015
DOI: 10.5539/ibr.v8n7p121
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Expectation from Online Retailers in Developing E-commerce Market: An Investigation of Generation Y in Bangladesh

Abstract: This paper aims to investigate the expectation from online retailers in the context of Generation Y, as the target market group in Bangladesh. It also examines the similarities and dissimilarities between the global online retail market trend and the target group. Volunteer final year university students conducted face to face survey using structured questionnaires. Primary data was collected using paper-and-pencil method where interviewee completed the form in most of the cases. This research found difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 36 publications
(32 reference statements)
1
12
0
3
Order By: Relevance
“…Not surprisingly Facebook tops the list. Similar to earlier study in the similar setup (Rahman, 2015), WhatsApp, Viber and Skype are found to be heavily used by all age groups and gender, but more by younger ladies and elder men. It seems Pinterest is gaining popularities among younger female group (age 18-25).…”
Section: Digital Communication Trait Of Gen Ysupporting
confidence: 87%
See 4 more Smart Citations
“…Not surprisingly Facebook tops the list. Similar to earlier study in the similar setup (Rahman, 2015), WhatsApp, Viber and Skype are found to be heavily used by all age groups and gender, but more by younger ladies and elder men. It seems Pinterest is gaining popularities among younger female group (age 18-25).…”
Section: Digital Communication Trait Of Gen Ysupporting
confidence: 87%
“…Self-administered paper-and-pencil intercept survey deemed appropriate for the purpose of this research as the target group is young adults (De Vries & Carlson, 2014). Similar to recent Gen Y study by Rahman (2015), final year students at BRAC University volunteered for the survey. Initial screening found their birth year is between 1991 and 1994.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations